Sanctuary and Patronal Feast in Salta: Spatialities and Temporalities in the Celebration of the Miracle (Argentina) - Nava Le Favi, Daniela (2025)
This investigation is based on an interdisciplinary approach strongly influenced by studies from the fields of anthropology and communication, with the aim of analyzing two core meanings that articulate spatiality and temporality in the devotion to the Lord and the Virgin of the Miracle in Salta. On the one hand, the notion of “Cathedral-Sanctuary” as a representation and geo-symbol of identity presents disputes/tensions of meaning (economic, symbolic) in its form of nomination between a provincial “inside” and “outside”. On the other hand, it is interesting to consider the phrase “Time of the Miracle” as a native category that interweaves places, festivals, institutional discourses, as well as ritual practices and the solidarity among believers of the cult. In both cases, these are spatial/territorial and temporal representations that manage to articulate diverse meanings, practices, and discourses of one of the most popular and ancient devotions in the country.